Phenotypic and Molecular Epidemiology of ESBL-, AmpC-, and Carbapenemase-Producing Escherichia coli in Northern and Eastern Europe - Sepp, Epp; Andreson, Reidar; Balode, Arta; Bilozor, Anastasia; Brauer, Age; Egorova, Svetlana; Huik, Kristi; Ivanova, Marina; Kaftyreva, Lidia; Kõljalg, Siiri; Kõressaar, Triinu; Makarova, Maria; et al. (Frontiers in Microbiology, 2019)
Extended-spectrum beta-lactamases (ESBL) and AmpC producing-Escherichia coli have spread worldwide, but data about ESBL-producing-E. coli in the Northern and Eastern regions of Europe is scant. The aim of this study has been to describe the phenotypical and molecular epidemiology of different ESBL/AmpC/Carbapenemases genes in E. coli strains isolated from the Baltic States (Estonia, Latvia, and Lithuania), Norway and St. Petersburg (Russia), and to determine the predominant multilocus sequence type and single nucleotide polymorphisms diversity of E. coli isolates deduced by whole genome sequencing (WGS). A total of 10,780 clinical E. coli strains were screened for reduced sensitivity to third-generation cephalosporins. They were collected from 21 hospitals located in Estonia, Latvia, Lithuania, Norway and St. Petersburg during a 5 month period in 2012. The overall prevalence of ESBL/AmpC strains was 4.7% by phenotypical test and 3.9% by sequencing. We found more strains with the ESBL/AmpC phenotype and genotype in St. Petersburg and Latvia than other countries. Of phenotypic E. coli strains, 85% contained confirmed ESBL genes (including blaCTX–M, blaTEM–29, blaTEM–71), AmpC genes (blaCMY–59, blaACT–12/–15/–20, blaESC–6, blaFEC–1, blaDHA–1), or carbapenemase genes (blaNDM–1). blaCTX–M–1, blaCTX–M–14 and blaCTX–M–15 were found in all countries, but blaCTX–M–15 prevalence was higher in Latvia than in St. Petersburg (Russia), Estonia, Norway and Lithuania. The dominating AmpC genes were blaCMY–59 in the Baltic States and Norway, and blaDHA–1 in St. Petersburg. E. coli strains belonged to 83 different sequence types, of which the most prevalent was ST131 (40%). In conclusion, we generally found low ESBL/AmpC/Carbapenemase prevalence in E. coli strains isolated in Northern/Eastern Europe. However, several inter-country differences in distribution of particular genes and multilocus sequence types were found.